Multiscale mixing analysis and modeling of biohydrogen production by dark fermentation. (December 2016) - Trad, Zaineb; Fontaine, Jean-Pierre; Larroche, Christian; Vial, Christophe
Abstract: Hydrogen production by dark fermentation (DF) from wastewater, food waste, and agro-industrial waste combines the advantages to be renewable, sustainable and environmentally friendly. But this attractive process involves a three-phase gas-liquid-solid system highly sensitive to mixing conditions. However, mixing is usually disregarded in the conventional strategies for enhancing biohydrogen productivity, even though H2 production can be doubled, e.g. versus of reactor design (0.6–1.5 mol H2 /mol hexose). The objective of this review paper is, therefore, to highlight the key effects of mixing on biohydrogen production among the abiotic parameters of DF. First, the pros and cons of the different modes of mixing in anaerobic digesters are described. Then, the influence of mixing on DF is discussed using recent data from the literature and theoretical analysis, focusing on the multiphase and multiscale aspects of DF. The methods and tools available to quantify experimentally the role of mixing both at the local and global scales are summarized. The 0-D to 3-D strategies able to implement mixing in fermentation modeling and scale-up procedures are examined. Finally, the perspectives in terms of process intensification and scale-up tools using mixing optimization are discussed with the issues that are still to be solved. Highlights: The effect of mixing is underestimated in dark fermentation of agro-waste. Non-ideal mixing conditions may enhance or impair biogas production. CFD and advanced measuring techniques are able to better elucidate mixing. Coupling CFD and biokinetic models remains theoretically and practically tough. Compartmental models based on CFD emerge as the best compromise.